Ambiguidade pronominal em orações adverbiais do português europeu: crianças vs. adultos - Lobo, Maria; Carolina Silva (Revista da Associação Portuguesa de Linguística, 2016)
This paper investigates how European Portuguese children interpret null and overt subject pronouns of adverbial clauses when there are two potential antecedents in the main clause, in order to find out how early the preferred readings are acquired in European Portuguese for each type of pronoun. Our results show that the control group of adults behaves as expected, choosing more often subject antecedents for null subjects and non-subject antecedents for subject pronouns, but children are predominantly at chance. The preferred interpretation for null subjects is acquired earlier than the one for overt pronouns and anaphoric contexts are acquired earlier than cataphoric ones. We attribute this developmental pattern to the fact that null pronouns are morphosyntactically more deficient and less dependent on semantic, discourse and prosodic factors, and to processing constraints related to the linear position of the antecedent.